(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Endometriosis may be defined as presence of functioning endometrium (glands and stroma) in sites other than uterine mucosa. The prevalence of endometriosis is about 10%. According to Nominato, cesarean section remains the most common surgical procedure related to the development of abdominal wall scar endometriosis1. But endometriosis sometimes presented to general surgeons as a lump in the abdomen. It can pose a diagnostic dilemma and should be in the differential diagnosis of lumps in the abdomen in females. Diagnosis is usually made following histological examination. This is a case report of abdominal wall endometriosis following cesarean section. This report discusses and evaluates the incidence, course, diagnosis, treatment and prevention of this condition. J Bangladesh Coll Phys Surg 2017; 35(3): 147-149